2020
DOI: 10.1074/jbc.ra120.014201
|View full text |Cite
|
Sign up to set email alerts
|

Cation channel conductance and pH gating of the innate immunity factor APOL1 are governed by pore-lining residues within the C-terminal domain

Abstract: The human innate immunity factor apolipoprotein L-I (APOL1) protects against infection by several protozoan parasites, including Trypanosoma brucei brucei. Endocytosis and acidification of high-density lipoprotein (HDL)-associated APOL1 in trypanosome endosomes leads to eventual lysis of the parasite due to increased plasma membrane cation permeability, followed by colloid-osmotic swelling. It was previously shown that recombinant APOL1 inserts into planar lipid bilayers at acidic pH to form pH-gated non-selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(67 citation statements)
references
References 39 publications
(72 reference statements)
4
62
0
Order By: Relevance
“…Over the past decade, epidemiologic, translational, and basic science research has led to innumerable insights about APOL1-associated nephrotic syndrome. We have a greater understanding of at-risk populations and the natural history of individuals affected [4,5,14,15], "second hits" that potentiate APOL1's penetrance [7,23], and cell structures and pathways that are involved in the disease's pathogenesis and progression [24][25][26][27]. At the same time, there are still many questions left on the table-answering them could ultimately contribute to improved patient care.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decade, epidemiologic, translational, and basic science research has led to innumerable insights about APOL1-associated nephrotic syndrome. We have a greater understanding of at-risk populations and the natural history of individuals affected [4,5,14,15], "second hits" that potentiate APOL1's penetrance [7,23], and cell structures and pathways that are involved in the disease's pathogenesis and progression [24][25][26][27]. At the same time, there are still many questions left on the table-answering them could ultimately contribute to improved patient care.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that additional protein domains and an extended bilayer membrane model is necessary for this behavior of the protein. The protonation status of D348 within the predicted transmembrane (TM) domain of APOL1-G0 C-terminus (D337-E335) is involved in pH gating function (46) and the G1 and G2 variants demonstrated increased cation channel activity in phospholipid vesicles (48). This predicted TM region in the C-terminus forms an α-helix with similar residue orientation in our NMR model.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the amphipathic helical membrane addressing domain (MAD) located N-terminal to the SRA-interacting C-terminal region of APOL1 proteins has been postulated to be a pH sensor and acts as a “hinge” structure between the C-terminus of APOL1 and the rest of the protein (41,51). APOL1 is known to localize to the endosomal and lysosomal compartment (6,18,19,50,52) and exposure to low pH could stabilize the membrane localization (46,47), given the presence of bis(monoacylglycero)phosphate and phosphatidylinositols in the slightly negatively charged endolysosomal membranes (53,54). This conformation can expose the C-terminal region of APOL1 to the cytoplasm, where interaction with SNAREs and other effector proteins is feasible.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent report, bioinformatic studies suggested that G1 and G2 altered ion channels' structural configuration in plasma membranes, resulting in K + efflux [70]. The influx of sodium and calcium by cation-selective pores could also enhance K + efflux [72,73]. Additionally, RRV-induced opening of the mitochondrial permeability transition pore has also been demonstrated to cause cell death [74].…”
Section: A Gain Of G1/g2 Toxic Functionmentioning
confidence: 99%